SSRMMD: A Rapid and Accurate Algorithm for Mining SSR Feature Loci and Candidate Polymorphic SSRs Based on Assembled Sequences - Gou, Xiangjian; Shi, Haoran; Yu, Shifan; Wang, Zhiqiang; Li, Caixia; Liu, Shihang; Ma, Jian; Chen, Guangdeng; Liu, Tao; Liu, Yaxi (Frontiers in Genetics, 2020)
Microsatellites or simple sequence repeats (SSRs) are short tandem repeats of DNA widespread in genomes and transcriptomes of diverse organisms, and used in various genetic studies. Few software programs are available for mining SSRs can be further used to mine polymorphic SSRs, and these programs have poor portability, strong dependence, slow computational speed, and low marker development rates. This study aimed to develop an algorithm named Simple Sequence Repeat Molecular Marker Developer (SSRMMD), which uses improved regular expressions to rapidly and exhaustively mine SSR feature loci from any size assembled sequence. To mine polymorphic SSRs, SSRMMD uses a novel three-stage method to assess the conservativeness of SSR flanking sequences and then uses the sliding window method to fragment each assembled sequence to assess its uniqueness. Furthermore, molecular biology assays supported these polymorphic SSRs identified by SSRMMD. SSRMMD is implemented in the Perl programming language and can be downloaded from https://github.com/GouXiangJian/SSRMMD.